Neuropsychologiczne aspekty percepcji muzyki - Czernecka, Karolina (Res Facta Nova, 2018)
The article reviews selected neuropsychological studies on brain correlates of music perception. First, the role and specialization of auditory cortex is discussed, focusing on differences between primary/secondary cortices as well as hemispheric asymmetry. Second, brain structures giving rise to emotional experiences during music listening are discussed, along with several possible explanatory mechanisms. Third, studies showing strengthened relationships between motor and auditory areas of the brain are demonstrated in the context of relative easiness of music to organize actions. The last part of the article focuses on the role of prefrontal cortex in building musical expectations and error perception. The influence of additional variables, such as listener’s musical training, on the observed effects is also discussed.